A Global Picture of School Social Work in 2021 - Marion Huxtable (International Journal of School Social Work, 2022)
The article provides a global picture of school social work in 2021 using data gathered by the International Network for School Social Work. School social work is a growing specialty around the world. There are school social workers practicing in more than 50 countries. School social workers support students' educational success, especially those who are marginalized by poverty, oppression, disability and other personal or social problems. Ideally school social workers practice within a multi-disciplinary team to address wide-ranging barriers to education and participate in preventive programs for all students. The article describes the growth of school social work around the world, various models of practice, the role of specialty professional associations, training and standards, and the growth of school social work literature. Changes in the role and practice of school social work since the COVID-19 pandemic of 2020/2021 are included. International communication among school social workers has grown via publications, conferences and the International Network for School Social Work, and continues to assist expansion of the specialty around the world. Implications for the future of social work in education are discussed, a list of national school social work associations is provided and references include literature on school social work from various countries.
Keywords: school social work; international